Identifying long-term effects of using hydropower to complement wind power uncertainty through stochastic programming. (1st November 2019) - Xu, Bin; Zhu, Feilin; Zhong, Ping-an; Chen, Juan; Liu, Weifeng; Ma, Yufei; Guo, Le; Deng, Xiaoliang
Graphical abstract: Highlights: A martingale model for capturing the evolution of forecasting uncertainty of wind energy. Stochastic programming models for determining operation strategies of hydro-wind hybrid system. Tradeoff effects and influencing mechanism between hydropower and wind energy identified. Case study that optimizes the integrated operation policies of hydro-wind hybrid system. Abstract: Integrated operation of hydropower and wind power, which exploites the former's regulation flexibility to complement the uncertainty of the latter, enhances the utilization efficiency of wind power at the expense of deteriorating long-term hydropower energy production. This study identified the tradeoff effects of hydro–wind integrated operation by establishing a framework of coupling models. A martingale model that captures the evolution of forecasting uncertainty was used to generate synthetic scenarios of uncertain load demand. A stochastic programming model for integrated operation was established by tracking the influence of wind power uncertainty. A deterministic simulation model for independent operation was developed to derive independent operation strategies. By comparing the differences in operation strategies systematically, we analyzed the optimization and influencing mechanisms through groups of numerical experiments. A hypothetical case study based on the operation of the electrical system of the Three Gorges Dam project in China during the drawdown season revealed the following. (1) The positive effect of reducing wind energy shortfall and curtailment is determined by the ability of regulated hydropower to track the uncertainty of wind power output. (2) The negative effect primarily reduces the end storage and the stored energy of hydropower, thereby increasing the risk of future water/energy shortages and reducing reliability. (3) The positive effect on wind power presents a varied regime, whereas the negative effect on hydropower increases (decreases) with uncertainty level and inflow level (as the initial reservoir storage increases). The proposed methodology provides new insights into quantifying the effects of hybrid hydro–wind operation to inform decision-making.